Do Reservation Wages Really Decline? Some International Evidence on the Determinants of Reservation Wages - John T. Addison; Mário Centeno; Pedro Portugal (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
Using cross-country data, we investigate the determinants of reservation wages and their course over the jobless spell. Higher unemployment benefits lead to higher reservation wages. Further, again consistent with the basic search model, repeated observations on the same individual provide scant evidence of declining reservation wages.
Keywords: J64; J65; 330; Reservation wages; probability of reemployment; unemployment benefits; arrival rate of job offers